Study of Dry Sliding Wear Characteristics of Corundum Reinforced Aluminium Alloy Matrix Composites - Singh Mann, Vikasdeep (My University, 2022)
The present work is focused on studies undertaken to improve the tribological properties of different corundum reinforced aluminium matrix composites (AMCs). The subject matter resulting out of the present study has been arranged in six chapters in this Ph.D. thesis. The outline of the chapters is as follows: ➢ Chapter 1: The chapter introduces the basic terms involved in the present research viz. composites, the classifications of composites, etc. This chapter discusses the need and benefit of AMCs and also presents the origin of the present research work. ➢ Chapter 2: This chapter presents a detailed review of literature on the processing and tribological properties of AMCs. The literature is divided into two main sections viz. wear behaviour of AMCs at room temperature and wear behaviour of AMCs at elevated temperatures. Further, in these two sections the literature is further classified into three groups viz. synthetic mineral reinforcement, natural mineral reinforcement, and hybrid mineral reinforcement. The chapter also brings forth the summary of the existing literature and also the main gaps in the existing literature in their field of work. ➢ Chapter 3: The chapter presents a brief description of materials used in the present study. The chapter also brings forth the methodology adopted for the processing of the composites. the chapter also discusses the equipment used for fabrication of AMCs, characterization of the processed AMCs (XRD, optical microscopy, SEM, EDS), and different mechanical tests (microhardness and Brinell hardness) done for the processed AMCs to fulfil the basic objectives mentioned in this chapter. ➢ Chapter 4: The chapter presents the results of wear analysis of single range particles (SRP) at room temperature and at elevated temperatures. The chapter discusses the microstructural investigation of base material and SRP reinforced corundum AMCs. The microstructural analysis revealed a uniform particle distribution with good structural refinement. EDS analysis of corundum particles showed the peaks of aluminium and oxygen. This confirmed the purity of corundum particles used in the study. Next, XRD analysis of base alloy and composites indicate the peaks of aluminium, silicon and aluminium-copper. In addition to this, composites also show the presence of corundum particles and sillimanite. Sillimanite is a reaction product of the interfacial reactions of the matrix and corundum particles. Further, the chapter also discusses the results pertaining to hardness, wear, and friction analysis of base alloy and composites at room temperature. The hardness and wear resistance of the composites increased with increase in the concentration of corundum particles. High microhardness values were obtained at the particle-matrix interface of SRP AMCs which indicated that the methodology adopted for processing of AMCs was very effective. Brinell hardness of SRP AMCs reinforced with 20 wt. % fine particles (1–20 μm) was comparable (only 7% lower) than the commercial grade cast iron used in brake rotor applications. The wear rate of the SRP composites decreased with decrease in corundum particle size. The best wear rate behaviour was displayed by SRP AMCs reinforced with 20 wt. % fine particles (20SRP-F) composite with a reduction of 58% and 59% in wear rate over the base alloy for the contact pressure of 1 MPa and 1.4 MPa respectively. Further, for the contact pressure of 1 MPa and 1.4 MPa, the wear rate of the composite was 7% and 6 % higher to the cast iron specimen. At room temperature, the coefficient of friction of the 20SRP-F composites was 40% and 41% lower at the contact pressure of 1 MPa, and 1.4 MPa respectively. Next the coefficient of thermal expansion of 20SRP-F composite was 50% lower than the base alloy. For the operating temperature of 200 ℃ and contact pressure of 1 MPa and 1.4 MPa, the meansteady-state wear rate of 20SRP-F composites was 59% and 67% lower than that of base alloy. Also, the wear rate of 20SRP-F AMCs was 3% higher than the cast iron sample. The coefficient of friction of 20SRP-F AMCs operating temperature of 200 ℃ and contact pressure of 1 MPa and 1.4 MPa, the COF of 20SRP-F composites was 44% and 45% lower than the base alloy. The COF of grey cast iron specimen at operating temperature of 200 ℃ and applied pressure of 1 MPa and 1.4 MPa was 3% and 6% higher than grey cast iron specimen respectively. Lastly, SEM analysis of wear tracks and wear debris indicated abrasive wear mechanism whereas for high contact pressure, delamination wear mechanism was dominant. ➢ Chapter 5: The chapter presents the results of wear analysis pertaining to dual reinforced particles (DRP) corundum particles at room temperature and elevated temperatures. Optical micrographs of DRP AMCs revealed uniform distribution of corundum particles in the matrix till 20 wt.% reinforcement level with no agglomeration of particles in the composites. This indicated that the microstructure refinement of the DRP composites was superior to the SRP composite formulations. Brinell hardness of the DRP AMCs with 20 wt.% particles in the ratio of fine:coarse as 4:1 (20DRP-4) was 4.5 % lower to the cast iron specimen used for brake rotor applications. Next, for the contact pressure of 1 MPa and 1.4 MPa, the wear rate of the 20DRP-4 composites was 62% and 61% lower to the base alloy. Also, the maximum wear rate of 20DRP-4 composites under contact pressure of 1 MPa and 1.8 MPa was 9 % and 6 % higher respectively compared to the commercial material. The addition of corundum particles decreased the coefficient of friction of the composites. Maximum reduction in COF value at the contact pressure of 1 MPa and 1.4 MPa was observed for 20DRP-4 composite was 47 % and 51 % over the base alloy. Further, for the contact pressure of 1 MPa and 1.4 MPa, the friction coefficient of 20DRP-4 AMCs, was 19% and 15% lower than the grey cast iron. The coefficient of thermal expansion of 20DRP-4 composites was 54% lower to the cast iron. Addition of corundum particles increased the transition temperature from 150 ℃ for the base alloy to 200 ℃ for the AMCs. For the operating temperature of 200 ℃ and contact pressure of 1 MPa and 1.4 MPa, the mean steady-state wear rate of 20DRP-4 composites was 69 % and 72 % lower than that of base alloy. Further, the wear rate of 20DRP-4 was 1.4 % higher than the grey cast iron specimen. At the temperature of 200 ℃ and contact pressure of 1 MPa, and 1.4 MPa, the friction coefficient of 20DRP-4 AMCs was 49 % and 54 % lower than the base alloy. further, the friction coefficient was 15 % and 25 % lower than grey cast iron specimen respectively. ➢ Chapter 6: This chapter summarizes the entire work and discusses the main conclusions drawn from the present study. The main results and findings of the experimental work are included in this chapter. The study revealed that the hardness, wear rate, and coefficient of friction of 20DRP-4 composites were superior to other composite formulations (both at room temperature and elevated temperatures). The results were also comparable to the grey cast iron used in brake rotor applications. Thus, 20DRP-4 composites can be used as a substitute material for brake rotor applications in light motor vehicles. The chapter also discusses the future scope of the present research work.
Keywords: Aluminum matrix composites; Corundom; DTG-TGA; Wear Debris Analysis; Wear track